ID 170 – Differences of spontaneous nocturnal neck myoclonus during REM and NREM Sleep. Neurophysiologic assessment with video PSG. Issue 3 (March 2016) - Banea, O.C.; García Parra, B.; Álvarez López-Herrero, N.
Abstract : Objective: We aimed at determining differences of Spontaneous Nocturnal Neck Myoclonus (SNNM) in REM and NREM sleep and to analyze the frequency of these type of myoclonus when limited to neck or generalized to limbs or axial. Methods: More than 40 patients (aged 6–77 years), remitted to our sleep laboratory with different sleep disorder, were consecutively analyzed. EEG artifact shorter than 200 ms corresponding to video PSG observed neck myoclonus, according to the method used by Frauscher et al., was analyzed. We analyzed EMG bursts in submentalis and tibial anterior together with video and EEG artifact. Every NM was studied at 30 and 5 s timeline. We performed descriptive analysis. NM related to respiratory event was rejected. When neck myoclonus was limited to the cervical segment we noticed the event as neck myoclonus (NM) and if the event was followed chronologically by other muscular segments of limbs or axial musculature we classified the event as propagated or generalized (NM GEN). Results: SNNM was observed in REM and NREM sleep phases. Conclusions: NM occurred more often during REM sleep than during NREM sleep. More studies are needed to demonstrate if a relation exists between the frequency of NM and medical conditions.